1999
DOI: 10.1093/intimm/11.5.753
|View full text |Cite
|
Sign up to set email alerts
|

An extrachromosomal switch recombination substrate reveals kinetics and substrate requirements of switch recombination in primary murine B cells

Abstract: Ig class switch recombination occurs in B lymphocytes upon activation, and is targeted to distinct switch (S) regions by cytokine-mediated induction of switch transcripts spanning the entire S region and the adjacent constant region gene segments. Using a novel type of switch recombination substrate, constructed according to the intron-exon structure of the IgH locus, but with heterologous elements, we here have tested the structural requirements for targeting and the kinetics of switch recombination in activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The preferential targeting of constant region genes indicates that class switch recombination occurs in a highly regulated process in HD‐derived cell lines. It has been shown for both murine and human B cells that class switch recombination is specifically directed not only with respect to onset and duration (Petry et al , 1999), but also with respect to the targeting of switch regions involved (Winter et al , 1987; Athan et al , 1989; Irsch et al , 1993, 1994). Particular switch regions are selected for recombination by cytokine‐induced transcription (Stavnezer‐Nordgren & Sirlin, 1986; Lutzker & Alt, 1988; for review see Lorenz & Radbruch, 1996; Hein et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferential targeting of constant region genes indicates that class switch recombination occurs in a highly regulated process in HD‐derived cell lines. It has been shown for both murine and human B cells that class switch recombination is specifically directed not only with respect to onset and duration (Petry et al , 1999), but also with respect to the targeting of switch regions involved (Winter et al , 1987; Athan et al , 1989; Irsch et al , 1993, 1994). Particular switch regions are selected for recombination by cytokine‐induced transcription (Stavnezer‐Nordgren & Sirlin, 1986; Lutzker & Alt, 1988; for review see Lorenz & Radbruch, 1996; Hein et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
“…‘Instability’ of the IgH loci of switching cells has been reported for endogenous IgH loci as well as for recombination substrates that had been introduced into cells activated for switch recombination (Ott & Marcu, 1989; Petry et al , 1999). DNA strand breaks are also introduced in Ig gene loci during other stages of B‐cell differentiation, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A Kozak sequence, initiation codon, FLAG tag and two unique restriction sites (AscI and ClaI) were inserted into the polylinker of pBI-EGFP, using the appropriate annealed oligonucleotides (details available upon request from D. Yablonski), to create pBI-FLAG. pBI-H-2K k was derived from pBI-FLAG, by replacing the EGFP coding sequence with a truncated form of the allelic mouse major histocompatibility complex antigen, H-2K k [37], isolated from the plasmid pMACS K k .II (Miltenyi Biotec GmbH, Germany). The Pak inhibitory fragments used in this paper are depicted in Figure 1.…”
Section: Plasmidsmentioning
confidence: 99%
“…Toward this end, many substrates have been developed for S recombination. Substrate studies have demonstrated the ability of S regions to stimulate recombination, and, like recombination of H chain genes, recombination of the substrates is usually increased by transcription (17)(18)(19)(20)(21). Recombination of substrates is usually better in B cell lines than in non-B cell lines (17-19, 22, 23).…”
Section: T He Ab H Chain Switch (S)mentioning
confidence: 99%